COMPARATIVE ANALYSIS OF PHYSICAL FITNESS OF MILITARY PERSONNEL OF DIFFERENT AGE CATEGORIES (Physical Culture and Sport: Scientific Perspective, 2025)
This article presents the results of a scientific study aimed at a comparative analysis of the impact of age on the level of physical fitness of military personnel undergoing basic general military training. The data representativeness for a comparative analysis between different age groups was ensured by a sample of 273 men aged 25 to 49 years. The homogeneity of the sample regarding the level of initial physical training was ensured by involving military personnel who were at the initial stage of military service. Non-parametric methods of mathematical statistics, namely the median test and the Kruskal-Wallis test, were used to ensure the reliability of the statistical results obtained.The analysis of the results of the test exercises, carried out using non-parametric methods of statistical analysis, did not reveal statistically significant differences between neighboring age groups in the indicators of strength, endurance, speed, and agility (χ² = 34.13 - 4.36, p > 0.05). However, the analysis of the distribution of physical fitness levels showed that with age, there is a gradual decrease in the percentage of military personnel with a high level of physical fitness, from 82.4% in the 25-29 age group to 42.6% in the 45-49 age group. At the same time, the percentage of military personnel with a low level of physical fitness increases from 8.8% to 40.7% in the corresponding age groups.The results of the study emphasize the relevance of the topic and the need to develop differentiated physical training programs adapted to the age characteristics of military personnel. The data obtained can be used to optimize the process of basic general military training in order to increase the level of physical readiness of military personnel of different age categories. Further research may be aimed at studying the impact of other factors, such as the specifics of military specialization and individual characteristics, on the physical fitness of military personnel.These findings highlight the critical importance of age-adapted training protocols in sustaining optimal physical readiness across diverse military cohorts. This study establishes a foundation for future research aimed at elucidating the multifaceted factors that influence physical performance within military populations.
Keywords: military personnel; physical qualities; basic general military training; level of physical fitness